Lipo-Based Vaccines as an Approach to Target Dendritic Cells for Induction of T- and iNKT Cell Responses - Stolk, Dorian A.; de Haas, Aram; Vree, Jana; Duinkerken, Sanne; Lübbers, Joyce; van de Ven, Rieneke; Ambrosini, Martino; Kalay, Hakan; Bruijns, Sven; van der Vliet, Hans J.; de Gruijl, Tanja D.; van Kooyk, Yvette (Frontiers in Immunology, 2020)
In this study we developed a liposome-based vaccine containing palmitoylated synthetic long peptides (SLP) and alpha galactosylceramide (αGC) to specifically target dendritic cells (DC) for activation of both innate (invariant natural killer T-cells [iNKT])and adaptive (CD8+ T-cells) players of the immune system. Combination of model tumor specific antigens (gp100/MART-1) formulated as a SLP and αGC in one liposome results in strong activation of CD8+ and iNKT, as measured by IFNγ secretion. Moreover, addition of lipo-Lewis Y (LeY) to the liposomes for C-type lectin targeting increased not only uptake by monocyte-derived dendritic cells (moDC), dermal dendritic cells and langerhans cells but also enhanced gp100-specific CD8+ T- and iNKT cell activation by human skin-emigrated antigen presenting cells in an ex vivo explant model. Loading of moDC with liposomes containing LeY also showed priming of MART-126-35L specific CD8+ T-cells. In conclusion, chemically linking a lipid tail to a glycan-based targeting moiety and SLP combined with αGC in one liposome allows for easy generation of vaccine formulations that target multiple skin DC subsets and induce tumor antigen specific CD8+ T- and iNKT cells. These liposomes present a new vaccination strategy against tumors.